If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -56 = -1x + 6x + 4 Reorder the terms: -56 = 4 + -1x + 6x Combine like terms: -1x + 6x = 5x -56 = 4 + 5x Solving -56 = 4 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -56 + -5x = 4 + 5x + -5x Combine like terms: 5x + -5x = 0 -56 + -5x = 4 + 0 -56 + -5x = 4 Add '56' to each side of the equation. -56 + 56 + -5x = 4 + 56 Combine like terms: -56 + 56 = 0 0 + -5x = 4 + 56 -5x = 4 + 56 Combine like terms: 4 + 56 = 60 -5x = 60 Divide each side by '-5'. x = -12 Simplifying x = -12
| 3/10=30/100 | | 13-6x=55 | | x^2-52=9x | | 6-2x=32 | | 59+7x=61+5x | | 2x-6=15-5x | | C+2c+3=8-2 | | (x)-7=29 | | 330=t^2 | | 2y^4+18y^3+54y^2+54y-288=0 | | 61-8x=205 | | 8x-9=-9+8x | | 3y-5+y+21=6y+20-4y | | 8x/12=1 | | 11*22/1 | | 11*1/22= | | -7(-3+5x)=-119 | | (x+2y)dx+(2x-y)dy=0 | | 8r-(5-3r)=5+r | | 11*1/22 | | 14+16(m+6)=-8 | | 18x^2+22x+21=0 | | -56=-20-6x | | 9k+35=4k | | 5(-10-6x)=70 | | -34=20-9x | | B=67-34+15 | | (3x-3)(5x-6)=0 | | 190=-y+92 | | -3(-2x+8)=18 | | 3.3x+52.2=18.0-8.1x | | -17-3x=-44 |